Caracterização anatômico-fisiológica e molecular da compatibilidade reprodutiva de ameixeiras japonesa - Conti, Daniela de (2012)
The Japanese plum (Prunus salicina Lindl.) is a fruit of great prominence worldwide. In Brazil, one of the most widely cultivated species of plum, because it presents climatic conditions favorable to its cultivation. However, some factors limit the increase in domestic production of plum trees, among them stands out the gametophytic self-incompatibility, due to the presence of a multiallelic codominant locus, containing the so-called S-alleles. Thus, the objective of this study was to identify physiologically and molecularly S-alleles of Japanese plum cultivars related to gametophytic self-incompatibility. For physiological characterization were carried out controlled pollination experiments in the experimental field of Embrapa, Clima Temperado (Pelotas/RS) and the pollination in vivo in laboratory, three cultivars of Japanese plum (América, Gulf Rubi and Gulf Blaze) which were evaluated fruit set and pollen tube growth (CTP), respectively. For molecular characterization, experiments were performed in the Laboratory of Plant Tissue Culture and Molecular Characterization, (UFPel / RS). To this end, we analyzed 19 Japanese plum cultivars by Polymerase Chain Reaction (PCR) with two pairs of specific primers for amplification of S-alleles. Crossings 'Gulf Blaze' x Gulf Rubi' Gulf Rubi x 'Gulf Rubi' and 'Gulf Rubi' x 'Gulf Blaze' had a fruit set of 11.36%, 3.84% and 9.94% respectively. In vivo pollination CTP reached the egg or ovarian in these crosses, with the exception of self-pollination of 'Gulf Rubi'. There was no fruit set in the field, self-pollination in 'América' and 'Gulf Blaze' and crossing 'América x' Pluma 7 '. The CTP in these crosses did not reach the egg, with the exception of self-pollination of 'Gulf Blaze'. Only the cross between 'América' x 'Pluma 7' are incompatible, and America is a self-incompatible cultivar. In amplification of S-alleles was possible to obtain the effective characterization of alleles-S of cultivars studies, as well as, the choice of pollinating more compatible with the cultivars producing. The cultivars América and Santa Rosa; Blood Plum, Wickson, Rosa Mineira, Estrela Púrpura and Planta 21 showed incompatibility between them.